Association between intakes of macro and micro nutrients and serum lipid profiles among Jordanian adults: a preliminary study - Tayyem, Reema; Hijjawi, Nawal S.; Al-Awwad, Narmeen; Nimer, Nisreen A.; Agraib, Lana M.; Allehdan, Sabika S.; Al-Radaideh, Ali M. (Progress in Nutrition, 2018)
Dyslipidemia is one of the most important risk factors for cardiovascular disease. Diet is considered as a major contributor for developing dyslipidemia. This study aimed to assess the intakes of macro- and micro-nutrients with serum lipid profile in disease-free adults. A convenient sample of 167 adults was recruited in this cross-sectional study. Serum lipid profile including total cholesterol, triglycerides (TG), low-density lipoprotein cholesterol LDL-C and high-density lipoprotein cholesterol HDL-C were measured. Nutrients and food groups consumption was assessed using a validated quantitative Food Frequency Questionnaire. The findings revealed different significant differences between the levels of total energy intake and macronutrients contribution to energy with serum lipid profiles. Cholesterol serum level was significantly higher among individuals with the highest energy intake (P=0.03), and was significantly lower with highest energy intake from trans-fatty acids (P=0.02). HDL-C tertiles were significantly associated with of percentage of energy from protein (P=0.04). Serum total cholesterol and LDL-C levels were significantly different with vitamin K intake levels (P=0.03). The intake of meat, fish, eggs, and beans was significantly different among HDL-C tertiles. (P=0.04). Many possible associations between Jordanian diet components and serum lipids were reported which indicates that diet is an important factor that should be considered when preventive or treatment strategies are implemented.